ANTISPERM ANTIBODIES IN SERUM AND CERVICAL MUCUS OF NORMAL AND REPEAT BREEDING COWS - SARMA, D K; BAISHYA, N; SHARMA, D K; DEKA, B C; BHUYAN, D (The Indian Journal of Animal Reproduction, 2023)
Indirect ELISA was performed to determine the antisperm-antibodies (asp-abs) in serum andcervical mucus from 14 normal and 53 repeat breeding crossbred cows .85.71% sera and 78.57%cervical mucus from normal breeding cows showed asp-abs titre of 1 :160 and 1 :40, respectively .Onthe other hand 100% cows repeating 3-5 times or more showed the presence of asp-abs in serumand mucus with the titre of 1 :3120 and 1: 1280, respectively. The significant observations made underthis study were that although a good proportion of normal cyclic cows were positive for asp-abs butwith lower level of titer in serum and mucus. The cows having more unsuccessful inseminationsshowed higher asp -abs with high titre in serum and mucus.
Keywords: Cross bred cows; Repeat breeding; Anti sperm antibodies; Serum and Cervical mucus